The antimicrobial activity of ephedrine and admixture of ephedrine and propofol: an in vitro study - Serkan Tulgar; Elcin Akduman Alasehir; Onur Selvi (Brazilian Journal of Anesthesiology, 2018)
Introduction: Propofol and Ephedrine are commonly used during anesthesia maintenance, the former as a hypnotic agent and the later as a vasopressor. The addition of propofol to ephedrine or administration of ephedrine before propofol injection is useful for decreasing or preventing propofol related hemodynamic changes and vascular pain. This in vitro study evaluated the antibacterial effect on common hospital-acquired infection pathogens of ephedrine alone or combined with propofol. Material and method: The study was performed in two stages. In the first, the Minimum Inhibitory Concentration of propofol and ephedrine alone and combined was calculated for Escherichia coli, Enterococcus faecium, Staphylococcus aureus, Pseudomonas aeruginosa, and a clinical isolate of Acinetobacter spp. at 0, 6, 12 and 24 h, using the microdilution method. In the second stage, the same drugs and combination were used to determine their effect on bacterial growth. Bacterial solutions were prepared at 0.5 MacFarland in sterile 0.9% physiological saline and diluted at 1/100 concentration. Colony numbers were measured as colony forming units.mL−1 at 0, 2, 4, 6, 8, 10 and 12th hours. Results: Ephedrine either alone or combined with propofol did not have an antimicrobial effect on Escherichia coli, Enterococcus faecium, or Pseudomonas aeruginosa and this was similar to propofol. However, ephedrine alone and combined with propofol was found to have an antimicrobial effect on Staphylococcus aureus and Acinetobacter species at 512 mcg.mL−1 concentration and significantly decreased bacterial growth rate. Conclusion: Ephedrine has an antimicrobial activity on Staphylococcus aureus and Acinetobacter species which were frequently encountered pathogens as a cause of nosocomial infections. Resumo: Introdução: Propofol e efedrina são fármacos comumente usados durante a manutenção da anestesia, o primeiro como agente hipnótico e o segundo como vasopressor. A adição de propofol à efedrina ou a administração de efedrina antes da injeção de propofol é útil para diminuir ou prevenir alterações hemodinâmicas e dor vascular relacionadas ao propofol. Este estudo in vitro avaliou o efeito antibacteriano de efedrina, isolada ou em combinação com propofol, em patógenos comuns implicados em infecção hospitalar. Material e método: O estudo foi realizado em duas etapas. Na primeira, a concentração inibitória mínima (CIM) de propofol e de efedrina isolada e em combinação foi calculada para Escherichia coli, Enterococcus faecium, Staphylococcus aureus, Pseudomonas aeruginosa e um isolado clínico de Acinetobacter spp às 0, 6, 12 e 24 horas, usando o método de microdiluição. Na segunda etapa, o mesmo fármaco e sua combinação foram utilizados para determinar seus efeitos no crescimento bacteriano. As soluções bacterianas foram preparadas em soro fisiológico a 0,9% em 0,5 McFarland e diluídas a uma concentração de 1/100. Os números das colônias foram medidos como cfu.mL−1 às 0, 2, 4, 6, 8, 10 e 12 horas. Resultados: Efedrina isolada ou em combinação com propofol não apresentou efeito antimicrobiano sobre E. coli, E. faecium ou P. aeruginosa, um resultado semelhante ao de propofol. Porém, efedrina isolada e em combinação com propofol apresentou efeito antimicrobiano sobre Staphylococcus aureus e Acinetobacter spp, em concentração de 512 mcg.mL−1, e redução significativa da taxa de crescimento bacteriano. Conclusão: Efedrina tem atividade antimicrobiana em S. aureus e Acinetobacter spp, que são patógenos frequentemente identificados como causa de infecções nosocomiais. Keywords: Ephedrine, Propofol, Antimicrobial, Palavras-chave: Efedrina, Propofol, Antimicrobiano